Kajian Peningkatan Daya Saing Usaha Mikro Kecil dan Menengah di Kota Kupang - Thomas Ola Langoday; Marius Masri Sadipun (Jurnal Inovasi Kebijakan, 2016)
The existence of Micro, Small and Medium Enterprises (SMEs) simply cannot be doubted, because it proved able to survive and become a cog economy, especially after the economic crisis. The purpose of the study of improving the competitiveness of Micro, Small and Medium Enterprises in Kota Kupang are: 1). Identify the profile of Micro, Small and Medium Enterprises, 2). Identify the product value chain of Micro, Small and Medium Enterprises, 3). Analyzing the advantages of private and social benefits of products of Micro, Small and Medium Enterprises, 4). Analyzing the comparative and competitive advantages of products of Micro, Small and Medium Enterprises, 5). Identifying constraints faced by Micro, Small and Medium Enterprises, 6). Creating models, strategies and actions to improve the competitiveness of Micro, Small and Medium Enterprises. To improve the competitiveness of Micro, Small and Medium Enterprises in Kota Kupang, required the development of Micro, Small and Medium Enterprises with cluster models; through the program input pro, pro process, and pro output; with the following stages: a). Human resource development; technical assistance, empowerment groups, and advocacy, b).Upstream-downstream cluster program; processing, packaging and waste treatment; c).Supporting factors; access to markets, access to financing and supporting facilities. Cluster program can be applied to the commitment and cooperation between the Agency and the relevant stakeholders.